Bảng tổng hợp, tiếp thu, giải trình ý kiến góp ý của các bộ, ngành, địa phương về dự án Luật Thực hiện dân chủ ở cơ sở (lần 1) - Bộ Nội vụ (2022)
Toàn văn Bảng tổng hợp, tiếp thu, giải trình ý kiến góp ý của các bộ, ngành, địa phương về dự án Luật Thực hiện dân chủ ở cơ sở (lần 1)